Maxillary orthodontic expansion assisted by unilateral alveolar corticotomy and low-level laser therapy: a novel approach for correction of posterior unilateral cross-bite in adults - Caccianiga, Gianluigi; Lo Giudice, Antonino; Paiusco, Alessio; Portelli, Marco; Militi, Angela; Baldoni, Marco; Nucera, Riccardo (Journal of Lasers in Medical Sciences, 2019)
Introduction: The treatment of a true unilateral posterior crossbite often requires asymmetric maxillary expansion; however, this is challenging to achieve with conventional expansion methods because of several biomechanical limitations. In this paper, we introduce a new protocol for the treatment of a unilateral posterior crossbite in adults based on maxillary orthodontic expansion assisted by corticotomy and low-level laser therapy (LLLT) performed on the crossbite side. Methods: The study sample included 15 adults (8 females, 7 males) affected by a true unilateral posterior crossbite, with a mean age of 21.6 ± 3.1 years at the at the beginning of treatment. After the application of orthodontic appliances (palatal expander and self-ligating brackets), corticomy was performed at the buccal aspect of the crossbite side while LLLT was monthly administered up to the correction of the crossbite. The efficacy of the technique was evaluated through measurements performed on maxillary digital models. Results: All subjects reported successful correction of the posterior unilateral crossbite, and functional occlusion was achieved as well. The average expansion was greater at the crossbite side compared to the unaffected side and such difference was significant at the levels of first premolars (P < 0.05), second premolars (P < 0.05) and first molars (P < 0.05). Conclusion: Orthodontic maxillary expansion assisted by unilateral corticotomy and LLLT was effective in the treatment of the true unilateral crossbite.